If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(2x + 4) = 0 Reorder the terms: (4 + x)(2x + 4) = 0 Reorder the terms: (4 + x)(4 + 2x) = 0 Multiply (4 + x) * (4 + 2x) (4(4 + 2x) + x(4 + 2x)) = 0 ((4 * 4 + 2x * 4) + x(4 + 2x)) = 0 ((16 + 8x) + x(4 + 2x)) = 0 (16 + 8x + (4 * x + 2x * x)) = 0 (16 + 8x + (4x + 2x2)) = 0 Combine like terms: 8x + 4x = 12x (16 + 12x + 2x2) = 0 Solving 16 + 12x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(8 + 6x + x2) = 0 Factor a trinomial. 2((4 + x)(2 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-4, -2}
| x+2x+14=89 | | x^4-16x^2+48=0 | | t^2+8t-20=0 | | 3(4+x)=26+x | | 3v^2+20v+32=0 | | -25=3+4u | | x+1=2x+3 | | 0.7w-0.3w+0.1w=3 | | 8x-17=11+6x | | 6c^2+c=2 | | 17-8x=11+6x | | t^2+3t+2=0 | | 0+15= | | 5x=(4x-2)(m+7) | | 4x(3x+5)= | | 5w-5w= | | 3=7x+10 | | 16x^2+4=36 | | 4.2x-3=1-x | | (x+2)(x-3)=(x-4)(x+5) | | -2(x-3)=2 | | 16K^2-36= | | 7a^2+13x-2= | | 5m=17 | | 5x^2-22=-10x | | X^2+22x+5= | | 18+x+2x=39 | | 0=2x^4-5x^2+1 | | 5t+2(1-5t)= | | 90+x-24+x=180 | | X*2-6x-7=0 | | (25b-8)-6(4b+3)=-2 |